STRUKTUR KOMPOSISI TUMBUHAN BAWAH TEGAKAN JATI DI KEBUN BENIH KLON (KBK) PADANGAN BOJONEGORO - Nazilatun Nikmah; J Jumari; Erry Wiryani (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Undergrowth vegetation are bottom layer of the tree community. Community of undergrowth vegetation are always identical as the weeds that had been considered as a disturber and harm. When viewed from another perspective undergrowth is a component of diversity. This study aimed to analyze the structure of the composition and reviewing the use of plants from three different plots under cropping Tectona grandis in seeds clones garden (KBK) Padangan. Data were collected at three research stations are in plots 1983, 1988 and 1993 using the plot as much as 36 squared, each size of 1 m x 1 m. Undergrowth plants were obtained from three research stations is 19 species from 12 families. Family Fabaceae or legumes are most often found. The highest undergrowth had Importance Value Index (IVI) from plots 1983 and 1993 was Sentrosema (Centrosema pubescens) and on plots 1988 is grass (Brachiaria decumbens). Index of species diversity (H') in the three different research stations showed the diversity of species are moderate at the region. Values of similarity index (IS) undergrowth vegetation showed the plant community from three research stations are different.Keywords: Undergrowth vegetation, species diversity, KBK Padangan, vegetation Analysis